1992
DOI: 10.1007/bf00185852
|View full text |Cite
|
Sign up to set email alerts
|

A motion correction algorithm for an image realignment programme useful for sequential radionuclide renography

Abstract: The correction of organ movements in sequential radionuclide renography was done using an iterative algorithm that, by means of a set of rectangular regions of interest (ROIs), did not require any anatomical marker or manual elaboration of frames. The realignment programme here proposed is quite independent of the spatial and temporal distribution of activity and analyses the rotational movement in a simplified but reliable way. The position of the object inside a frame is evaluated by choosing the best ROI in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…There have been several methods reported for motion correction of radionuclide renograms. In 1992, De Agostini et al reported a method for re-aligning shifted renogram images by using statistical methods to select from a set of shifted ROIs the one that best represents the motion of features within the image[25]. Lee and Barber used affine transformation with decomposition to motion correct renograms [26].…”
Section: Background and Objectivesmentioning
confidence: 99%
“…There have been several methods reported for motion correction of radionuclide renograms. In 1992, De Agostini et al reported a method for re-aligning shifted renogram images by using statistical methods to select from a set of shifted ROIs the one that best represents the motion of features within the image[25]. Lee and Barber used affine transformation with decomposition to motion correct renograms [26].…”
Section: Background and Objectivesmentioning
confidence: 99%